Association between musculoskeletal disorders and healthcare expenditures among patients from the Brazilian public healthcare system - Codogno, Jamile Sanches [UNESP]; Turi, Bruna Camilo [UNESP]; Fernandes, Rômulo Araújo [UNESP]; Bonfim, Mariana Rotta [UNESP]; Pastre, Carlos Marcelo [UNESP]; Monteiro, Henrique Luiz [UNESP] (My University, 2015)
Study Design: Cross-sectional. Objectives: (i) To identify the prevalence of musculoskeletal disorders, (ii) to identify musculoskeletal disorders correlates and (iii) to identify the existence of relationship between musculoskeletal disorders and healthcare expenditures in adults attended to by the public healthcare system. Methods: Crosssectional study involving 963 adults (over 50 years of age and of both sexes) treated in basic healthcare units (BHU). The participants answered questionnaires about self-reported morbidity, economic condition, musculoskeletal symptoms, occupational activity behavior, physical therapy consultation and prescription drugs purchased. Weight and height were obtained for body mass index computation. Healthcare expenditures in the last 12 months were computed. Results: The prevalence of musculoskeletal symptoms was 65%. Patients diagnosed with musculoskeletal system/connective tissue diseases (OR= 4.11 [2.98 - 5.67]) and people who needed to lift loads at work (OR= 1.45 [1.27 - 1.66]) presented higher likelihood to report the outcome. Moreover, occurrence of musculoskeletal symptoms in shoulders, low back, knees and ankles/feet were positively related to increased prescription drugs used and medical consultations. Conclusion: There is a high occurrence of musculoskeletal symptoms in Brazilian patients, which is affected by sex and occupational activity, and is positively related to increased healthcare expenditures.
Keywords: Costs and cost analysis; Motor activity; Musculoskeletal pain; Public health